Ethical Dimensions of Music Information Retrieval Technology. Issue 1 (21st September 2018) - Holzapfel, Andre; Sturm, Bob L.; Coeckelbergh, Mark
This article examines ethical dimensions of Music Information Retrieval (MIR) technology. It uses practical ethics (especially computer ethics and engineering ethics) and socio-technical approaches to provide a theoretical basis that can inform discussions of ethics in MIR. To help ground the discussion, the article engages with concrete examples and discourse drawn from the MIR field. This article argues that MIR technology is not value-neutral but is influenced by design choices, and so has unintended and ethically relevant implications. These can be invisible unless one considers how the technology relates to wider society. The article points to the blurring of boundaries between music and technology, and frames music as "informationally enriched" and as a "total social fact." The article calls attention to biases that are introduced by algorithms and data used for MIR technology, cultural issues related to copyright, and ethical problems in MIR as a scientific practice. The article concludes with tentative ethical guidelines for MIR developers, and calls for addressing key ethical problems with MIR technology and practice, especially those related to forms of bias and the remoteness of the technology development from end users.